Sport Betting Among Students of Federal University Wukari, Taraba State, Nigeria - Shipurut, Geoffrey Nanbal; Dauda, Gbana Nkpujire-ekah (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2024)
The recent ease access to online betting platforms and the perceived potential for financial gain contribute to the popularity of sports betting among students. However, there are concerns about the impact of sports betting on students’ academic performance and overall wellbeing. This papers discussion is centered on ‘sport betting among students of Federal University Wukari. The paper used a descriptive survey research design. A sample size of 200 respondents were purposefully selected for the study. Responses from the questionnaires were analyzed using descriptive statistics of frequency counts and percentages. The paper revealed that sports betting is more than just a recreational activity for many students; it has significant negative impacts on their concentration, financial management, and mental health. the paper also revealed that frequent and prolonged engagement in sports betting is associated with potential negative impacts on students' financial well-being, academic performance, and social interactions. The paper recommended that Educational institutions should provide access to counseling and support services specifically targeting students affected by the emotional and psychological impacts of sports betting. Also, educational programs focused on financial literacy and responsible gambling should be introduced to help students better manage their finances and understand the risks associated with betting. These programs could include workshops on budgeting, the consequences of risky financial behavior, and strategies for avoiding financial pitfalls related to gambling.